Comparison of the quality of bee pollen stored frozen and dried - Anjos, Ofélia (2020)
Bee pollen is a healthy food product that is usually consumed as dried crunchy pellets. Even so, i tis possible consume this product as frozen fresh pellets. In this study we present the effect of the storage conditions on the chemical composition of different monofloral bee pollen samples and the changes on the lipid profile of bee pollen samples submited to freezing and drying conservations methods. Nine bee pollen samples with different botanical origins were harvested in the Northeast of Portugal and divided into two different groups: the first one was frozen at -20ºC and the second was dried at 42ºC until the moisture ranged 6 to 8%. The following parameters were analysed and compared amongst the two storage methods: pH, water activity, total acidity and the content of fibre, ash, reducing sugars, protein, lipid and lipid profile, total phenols, total flavonoids, content of vitamin C, B-carotene and lycopene. Microbiological analyses were also made in order to certify if the product was in accordance with the standards for consumer`s safety. A two way analysis of variance was performed with two factors: species storage method. The differences in the botanical origin for furtemost of the analysed parameters are a significant factor explaining the variation between samples. Even though the differences on the botanical origin play a key role, the storage method was also found to be a highly significant factor influencing several analysed parameters namely: reducing sugars, lipid, total phenols, total flavonoids, content of vitamin C, B-carotene and lycopene. Frozen bee pollen presented a significant higher concentration of some dietary. From nutritional point of view, our results suggest that is better consume bee pollen frozen at -20ºC in comparision to that dried in an electric oven. However, it is important to define very well the conditions during the frozen process to ensure a lower microbiological contamination that is easier obtain when the bee pollen is dried.